Pelatihan Pencatatan Akuntansi Perusahaan Dagang Kepada Siswa SMA Kristen Yusuf - Sufiyati, Sufiyati; Goenawan, Melvin Vanwi; Lie, Eric Bryan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Accounting knowledge is always used in business activities to measure company performance. By equipping young people with accounting knowledge, the younger generation can prepare themselves to face challenges in this era. The problem faced by partners is the limited time in economics and finance class hours, resulting in grade XII students being unable to study trading company accounting materials more deeply, especially for practice problems. Accounting knowledge shapes them to think logically and more carefully. This accounting knowledge becomes provision and foundation for them, as the younger generation, in managing finances and in making decisions related to their finances. The community services (PKM) activity method has several stages. Starting with compiling a trading company accounting module, providing theoretical briefing on trading company accounting accompanied by example problems, practice problems and quizzes. The PKM implementation method has 3 stages: preparation, implementation, and reporting. The preparation stage involves conducting surveys to partners to identify problems faced by partners. The implementation stage prepares modules and provides training accompanied by practice problems and quizzes. The reporting stage creates accountability reports to LPPM. The solution to partner problems is for the school to collaborate with the UNTAR PKM team to provide training conducted outside school hours to help students better understand the material. PKM activities were carried out offline from April 21 to May 5, 2025 at SMA Kristen Yusuf. The training proved effective, reflected in satisfactory quiz scores and student enthusiasm